2013
DOI: 10.1007/s00464-012-2753-y
|View full text |Cite
|
Sign up to set email alerts
|

Transoral endoscopic surgery versus conventional thoracoscopic surgery for thoracic intervention: safety and efficacy in a canine survival model

Abstract: This study demonstrated that the transoral approach was comparable to conventional thoracoscopic surgery for lung biopsy and pericardial window creation in terms of safety and efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Eliminating conventional abdominal incisions is considered to have a number of potential advantages including faster recovery and thus a shorter hospital stay, decreased postoperative pain, improved postoperative pulmonary function and improved cosmetic outcome. Previous studies have also confirmed the safety and benefits of VATS in thoracic cavity surgery (3,4).…”
Section: Introductionmentioning
confidence: 63%
“…Eliminating conventional abdominal incisions is considered to have a number of potential advantages including faster recovery and thus a shorter hospital stay, decreased postoperative pain, improved postoperative pulmonary function and improved cosmetic outcome. Previous studies have also confirmed the safety and benefits of VATS in thoracic cavity surgery (3,4).…”
Section: Introductionmentioning
confidence: 63%
“…Minimizing tissue trauma and subsequent stress response is a goal of surgery [ 42 ] and CRP is often included as an objective marker in studies investigating this response in dogs [ 37 , 42 , 43 , 45 ]. CRP has on several occasions been used in studies investigating new surgical procedures for the veterinary clinic [ 26 , 29 , 31 , 35 ], in studies using dogs as model for human disease [ 27 , 28 , 30 ], and in studies comparing different surgical procedures [ 32 , 34 ]. In the last group several studies have compared surgical trauma by comparing different surgical procedures in different tissues [ 9 , 33 ].…”
Section: Reviewmentioning
confidence: 99%
“…One study has, however, shown significant lower concentrations of CRP as a result of treatment with low doses of ketamine during and after surgery [ 40 ], as also demonstrated in humans [ 51 ]. Ketamine was included in the anesthetic protocols of 6 studies included in the review [ 22 , 27 , 28 , 32 , 34 , 41 ], and CRP concentrations in these studies could potentially be affected when compared to the remaining studies. However, other studies in human medicine have shown conflicting results [ 52 , 53 ] and the conclusions for dogs were all based on a single study affected by considerable risks of bias (Fig.…”
Section: Reviewmentioning
confidence: 99%
“…Lung biopsy and pericardial window creation were completed via a 12-mm incision over the vestibulum oris region. A comparative study of a transoral versus conventional thoracoscopic approach for thoracic intervention in a canine model was published in 2013 (45). The results demonstrated that the transoral approach is comparable to conventional thoracic surgery for lung biopsy and pericardial window creation in terms of safety and efficacy (45).…”
Section: Natural Orifice Transluminal Endoscopic Surgery (Notes) In Tmentioning
confidence: 99%
“…A comparative study of a transoral versus conventional thoracoscopic approach for thoracic intervention in a canine model was published in 2013 (45). The results demonstrated that the transoral approach is comparable to conventional thoracic surgery for lung biopsy and pericardial window creation in terms of safety and efficacy (45). However, a weakness of the transoral approach is the size of lung that can be removed is limited by the small incision at the vestibule oris region (46).…”
Section: Natural Orifice Transluminal Endoscopic Surgery (Notes) In Tmentioning
confidence: 99%